Antecedents of tourist loyalty in rural tourism: A PLS SEM and IPMA anaylsis - Basharat Hussain; S. Sumaira (Borneo Novelty Publishing, 2026)
Purpose – This study aims to examine the determinants of tourist loyalty in rural tourism, focusing on the relationships among cognitive image, perceived value, and tourist satisfaction in the Kashmir Valley.Design/Methodology/Approach – A quantitative approach was employed using data collected from 407 visitors. The study applied PLS-SEM and Importance-Performance Map Analysis to analyse structural relationships and evaluate the relative importance and performance of key constructs influencing tourist loyalty.Findings – The results indicate that cognitive image and perceived value significantly influence tourist satisfaction. However, only perceived value has a direct effect on tourist loyalty. The relationship between cognitive image and loyalty is fully mediated by satisfaction. Furthermore, IPMA results reveal that perceived value is the most critical determinant of loyalty but shows a relatively lower performance level compared to other factors, indicating a strategic improvement gap. These findings highlight that enhancing perceived value and maintaining high levels of satisfaction are essential to fostering tourist loyalty in rural destinations.Originality/Value – This study contributes to rural tourism literature by integrating structural and performance-based analysis to better understand loyalty formation. It provides practical insights for destination managers to prioritize perceived value enhancement strategies while sustaining tourist satisfaction to achieve long-term loyalty.